Strategi Konten Instagram @dprd.lomboktimur dalam Membangun Transparansi dan Kepercayaan Publik - Yuni Elmina; Iwan Joko Prasetyo; Harliantara Harliantara (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study analyzes the Instagram content strategy of the @dprd.lomboktimur account in building transparency and public trust in the regional legislative body. Social media has become a strategic tool for government institutions to communicate with the public, but its effectiveness depends heavily on the content strategy implemented. Based on analytical data from Toolzu.com for the 2025-2026 period, the @dprd.lomboktimur Instagram account had 417 followers, 136 posts, an engagement rate of 0.14%, and an average user activity of 1.96%. This study used a descriptive qualitative approach with digital content analysis and a literature review on government communication. The results show that the implemented content strategy still focuses on documenting internal activities (commission meetings, working visits) with the dominant keywords "East Lombok," "Commission," and "meeting." The low engagement rate indicates a lack of two-way interaction with the public. These findings suggest the need for content diversification, increased humanistic narratives, optimized posting times, and strengthened engagement strategies to build transparency and public trust more effectively.